A virus encephalitis - Trelles, J. O. (1953)
The problem of virus infections of the brain is very topical and has served as the official theme in several international scientific conferences. I remember, among the most recent, which was one of the points of the International Neurological Congress in Paris (1949); Estutgardt German Congress of Neurology (1951); and he was also addressed at the Congress of Medicine, London (July 1952) .